If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x+12=-2x+36
We move all terms to the left:
-3x+12-(-2x+36)=0
We get rid of parentheses
-3x+2x-36+12=0
We add all the numbers together, and all the variables
-1x-24=0
We move all terms containing x to the left, all other terms to the right
-x=24
x=24/-1
x=-24
| 12-5x=x+16 | | 2y+37=5-5y | | 9(p-4)=-13 | | 4=8c | | -2x+5+10=3x | | 3+3/2x+4=13 | | 11.24+0.1y=-1.5y+0.68 | | 4.40/323=x/398 | | 4x+5-6x+8=3x-7 | | 3x-55=100 | | -×-1=-1-x | | 19=-23+(2-p) | | x+3/5=-8 | | 6p+2+p-4=8p-8 | | -2x+4=-2x+7 | | 8/45x=8 | | 8r–10=62 | | 13w-3=-4 | | 3w-w-w=18 | | 2(x+6)=x-26 | | 5p-1=5p+3p-8 | | 5x=45+15 | | X=11=4+6x | | 8+6m-8=-18 | | |5-2d|=7 | | x-0.2=3.8 | | z/3×3=-30 | | 2(u+8)=20 | | 8a-(-6a)-3a-6a=(-20) | | 4x+12+6x-2+50=180 | | 2s=96 | | 5x-32=3x+12 |